Evaluation of Efficacy of Adjuvant Radiotherapy in Well-Differentiated Liposarcoma Patients with Positive Surgical Margins: A Population-based Study. (8th September 2022) - Wang, Haoran; Chen, Boran; Cen, Ying; Chen, Junjie
Abstract : Background . The use of adjuvant radiotherapy (RT) for well-differentiated liposarcoma (WD-LPS) patients with positive surgical margins is unclear. We aim to compare the overall survival (OS) and cancer-specific survival (CSS) of well-differentiated liposarcoma patients with positive surgical margins in an RT group and non-RT group. Methods . WD-LPS patients with positive margins from 2000 to 2018 were extracted from the Surveillance, Epidemiology, and End Results (SEER) database and divided into two groups: RT group and non-RT group. Kaplan–Meier survival analysis with the log-rank test was performed to evaluate the difference of overall survival (OS) and cancer-specific survival (CSS) between groups. Univariate and multivariate Cox proportional hazard analyses were performed to identify important prognostic factors of OS and CSS. Analyses were adjusted using propensity-score matching. Results . We identified 2549 patients: 377 (14.79%) with RT and 2172 (85.21%) without RT. The median age was 61 years, and the median follow-up time was 68 months. The log-rank test revealed that there was no significant difference of CSS between RT and non-RT groups (P = 0.81 ). The 5-year and 10-year CSS were comparable (P = 0.418 and P = 0.987 ). Additionally, the use of RT was neither an independent prognostic factor for OS nor CSS. Age, sex, tumor site, the use of chemotherapy were independent prognostic factors for OS after propensity score matching, while race and the tumor site were independent prognostic factors for CSS. Conclusion . Adjuvant RT had no significant improvement on OS and CSS of WD-LPS patients with positive surgical margins.